2001
DOI: 10.1074/jbc.m106226200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3-Kinase-dependent Pathways Oppose Fas-induced Apoptosis and Limit Chloride Secretion in Human Intestinal Epithelial Cells

Abstract: The epithelial lining of the intestine serves as a barrier to lumenal bacteria and can be compromised by pathologic Fas-mediated epithelial apoptosis. Phosphatidylinositol (PI)3-kinase signaling has been described to limit apoptosis in other systems. We hypothesized that PI3-kinase-dependent pathways regulate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 94 publications
0
21
0
Order By: Relevance
“…Recent reports have indicated that blockade of the PI 3-kinase pathway with inhibitors sensitized endothelial and epithelial cells to both Fas-and TNF␣-induced death (43,44), thus setting a precedent for the importance of the PI 3-kinase/Akt pathway in inhibiting stress-induced apoptosis. Our observations support this notion in that neutrophils incubated with the integrin-activating antibody VIM12 and the stress stimulus TNF␣ or anti-Fas IgM displayed a significant increase in apoptosis, which was shown to be directly linked to loss of Akt activity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have indicated that blockade of the PI 3-kinase pathway with inhibitors sensitized endothelial and epithelial cells to both Fas-and TNF␣-induced death (43,44), thus setting a precedent for the importance of the PI 3-kinase/Akt pathway in inhibiting stress-induced apoptosis. Our observations support this notion in that neutrophils incubated with the integrin-activating antibody VIM12 and the stress stimulus TNF␣ or anti-Fas IgM displayed a significant increase in apoptosis, which was shown to be directly linked to loss of Akt activity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The phosphoinositide 3-kinase (PI3K)/ Akt pathway plays a pivotal role in these mechanisms. Studies that evaluated Fas-mediated apoptosis of intestinal epithelial cells showed that the inhibition of PI3K sensitizes cells to Fas-induced apoptosis, whereas the constitutive expression of Akt protects cells from apoptosis (21). CK8/ 18-free hepatocytes from CK8-null mice were shown to be more sensitive than wild-type mouse hepatocytes to Fasmediated apoptosis after stimulation with Jo2, an agonistic antibody of Fas ligand (12).…”
Section: Cell Signalingmentioning
confidence: 99%
“…Further investigation is needed to determine the consequences of altered expression of CK18 on cellular function. Investigators have explored various post-translational modifications of CK18, including site-specific phosphorylation (16,19,21), OGlcN-arylation (18,19), and acetylation (20). These modifications regulate each other and determine the solubility, filament organization, and stability of CK8/18.…”
Section: Expression and Clinical Applications Of Ck18 In Cancer Exprementioning
confidence: 99%
“…Nevertheless, caspase 8 does not appear to be present in established focal adhesions, nor does caspase 8 activation occur during integrin ligation events during cell spreading. However, caspase 8 is not always activated by DR ligation and membrane recruitmentin fact, the activation of signaling molecules such as Akt (Abreu et al, 2001;Li et al, 2002;Thakkar et al, 2001) or PKC (Gomez-Angelats and Cidlowski, 2001;Miranti et al, 1999;Zhuang et al, 2001;Meng et al, 2002) suppresses activation of caspase 8 and may be involved in DR-mediated signaling to the NFκB, JNK or ERK1/2 pathways (Fig. 4).…”
Section: Do Integrins Communicate With the Ded?mentioning
confidence: 99%